POWTOON POP UP BOOK DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR PPKN SISWA KELAS 5 SD UPT SD NEGERI 101740 TANJUNG SELAMAT - Dwi Priyanti; Gabriela Anjelika Br. Sebayang; Ficha Aulia Nanda (Jurnal Binagogik, 2025)
This research is motivated by the limited use of learning media, and there are students who are not motivated in learning, one of which is on the material Pancasila in my life. The objectives of this study are: (1) to describe the process of developing the Powtoon Pop Up Book Digital learning media on the material of the form of objects and their changes. (2) to analyze the response of teachers in grade V to the practicality of the Powtoon Pop Up Book Digital learning media on the material of the form of objects and their changes. (3) to analyze the effectiveness of the Powtoon Pop Up Book Digital learning media on the learning outcomes of grade V students of SD 101740 Tanjung Selamat. The research method used is Research and Development (R&D), using the ADDIE model. The results of the study showed that the Powtoon Pop Up Book Digital learning media on the material Pancasila in my life had met the "Very Valid" category based on the score of 88% of the media validation results and 90% of the material validation results. The data from the response of class V A teachers obtained a score of 87% with the criteria "Very Practical". The data from the pre-test and post-test motivation questionnaires calculated using the Standard N-gain obtained a score of 0.82 with the category "High" and the percentage of N-gain Score obtained was 82.11 with the category "Effective". Based on the results of the study, the Powtoon Pop Up Book Digital learning media on the Pancasila material in my life in class V of SD Negeri 101740 Tanjung Selamat is very worthy of being used and developed further.